2013
DOI: 10.3390/ijms141224126
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Activity of the FUT1 Gene Promoter Region in Pigs

Abstract: This study aims to provide a theoretical basis on the regulatory mechanism of the α-l,2-fucosyltransferase (FUT1) gene in pigs by analyzing the transcriptional activity of its promoter region. On the basis of the previously obtained promoter sequence, primers upstream and downstream of the gene were designed using the restriction endonucleases KpnI and HindIII respectively, and the recombinant plasmids of the pGL3-promoter were constructed by inserting promoter sequences with partially missing regions. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…In addition, HIF-1a expression was inversely correlated with FUT1/2 expression and cell surface fucosylation in PaTu-S cells, and in the colon cancer cell lines SW480 and HTC116, indicating that this effect is not restricted to PDAC cells. Our data are not directly in accordance with recent data which show that FUT1 transcription was elevated under hypoxic conditions in prostate cancer cells [31]. Whereas hypoxia is known to induce HIF-1a expression, the role of HIF-1a in the regulation of FUT1 was not investigated in the latter study, leaving the possibility open that other hypoxia-induced factors could be involved in the observed upregulation of FUT1 in prostate cancer [32].…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…In addition, HIF-1a expression was inversely correlated with FUT1/2 expression and cell surface fucosylation in PaTu-S cells, and in the colon cancer cell lines SW480 and HTC116, indicating that this effect is not restricted to PDAC cells. Our data are not directly in accordance with recent data which show that FUT1 transcription was elevated under hypoxic conditions in prostate cancer cells [31]. Whereas hypoxia is known to induce HIF-1a expression, the role of HIF-1a in the regulation of FUT1 was not investigated in the latter study, leaving the possibility open that other hypoxia-induced factors could be involved in the observed upregulation of FUT1 in prostate cancer [32].…”
Section: Discussioncontrasting
confidence: 79%
“…The mechanism by which HIF‐1α suppresses FUT1/2 expression has not been clarified in this work, and future studies are required to fully understand the function of this transcription factor in the suppression of α1,2‐fucosylation, and its relevance for cell migration and metastasis. Interestingly, results of studies on the transcriptional regulation of the pig FUT1 gene demonstrated that this gene possesses positive and negative regulatory elements in the upstream non‐coding region [31]. The negative regulatory area impaired transcription initiation even though abundant cis ‐acting elements and transcription factor‐binding loci were predicted in that specific area of the FUT1 promoter gene [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IPEC-J2 cells were transfected with recombinant plasmids pGL3-P1 and pGL3-P2 for 24 h (Zi et al, 2013), and dual luciferase assays were performed. The products were subjected to electrophoresis on a 1% agarose gel.…”
Section: Dual Luciferase Analysis Of Fut1 Promotersmentioning
confidence: 99%
“…Along with the rapid development and reduced costs of next-generation sequencing (NGS), high-throughput RNA sequencing (RNA-seq) has rapidly emerged as a major transcriptome profiling system to discover differentially expressed genes and novel transcripts (Garber et al 2011). So far, there have been some RNA-seq studies on human (Zi et al 2013), chicken (Katie et al 2013) and pig (Chen et al 2011). Also, RNAseq has been successfully employed in bovine embryo (Huang & Khatib 2010) and milk transcriptome investigations (Canovas et al 2010).…”
Section: Introductionmentioning
confidence: 98%